Prognostic Signature and Discrimination Signature of Lung Adenocarcinoma based on Pyroptosis-Related Genes - Li, Guo-Sheng; Lu, Hui-Ping; Gao, Li; Li, Jian-Di; He, Rong-Quan; Zhou, Hua-Fu; Chen, Shang-Wei; Liu, Jun; Fu, Zong-Wang; Kong, Jin-Liang; Zeng, Jiang-Hui; He, Juan; et al. (Combinatorial Chemistry & High Throughput Screening, 2023)
Background: The clinical value of pyroptosis-related genes (PRGs) in lung adenocarcinoma (LUAD) remains obscure. Objective: The study attempts to explore PRGs in LUAD, which will enable an understanding of LUAD from the perspective of PRGs. Methods: Lung adenocarcinoma patients were diagnosed using pathology, and their clinical information was collected from several public databases. A PRGs prognostic signature (PPS) for LUAD patients was established based on a multivariate Cox regression analysis. The differential expression of PRGs was identified using standardized mean differences in 6,958 samples. The area under the curve (AUC) was used to evaluate the predictive effects of the PPS to determine the survival rate of LUAD patients. Decision curve analysis was utilized to assess the clinical significance of the PPS in LUAD. Results: The PPS consists of five PRGs, namely CASP3, CASP9, GSDMB, NLRP1, and TNF. The prognostic effect of the PPS is evident in all the predicted one-, three-, and five-year survival rates (AUCs ≥ 0.58). The PPS represents an independent risk factor for the prognosis of LUAD patients (hazard ratio > 1; 95% confidence interval excluding 1). The PPS risk score can predict the prognosis of LUAD patients more accurately than PRGs of the PPS and multiple clinical parameters, such as age, tumor stage, and clinical stage. The decision curve analysis revealed that the nomogram based on the PPS and clinical parameters might result in better clinical decisions. Conclusion: The PPS makes it feasible to distinguish LUAD from non-LUAD. Thus, the underlying significance of the PPS in distinguishing LUAD from non-LUAD is promising.
Keywords: pyroptosis-related gene